2022
DOI: 10.1128/mbio.03869-21
|View full text |Cite
|
Sign up to set email alerts
|

The Psychrotrophic Pseudomonas lundensis, a Non- aeruginosa Pseudomonad, Has a Type III Secretion System of the Ysc Family, Which Is Transcriptionally Active at 37°C

Abstract: P. lundensis strains have been isolated from environments that are distinct and diverse in both nutrient availability and environmental pressures (cold food spoilage, Antarctic melt ponds, cystic fibrosis lungs). As a species, this bacterium can grow in diverse niches that markedly vary in available nutrients and temperature, and in our study, we show that these various strains share greater than 99% sequence similarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Interestingly, that bacterial species isolated from MPs in this study were previously found in both cold and non-cold environments, while most of the isolated bacterial species were similar to those found in other types of samples from cold polar and non-polar regions. For example, other researchers isolated Shewanella baltica [ 58 ], Pseudomonas lundensis [ 59 , 60 ], Pseudomonas leptonychotis [ 61 ], Carnobacterium funditum [ 62 ], Carnobacterium iners , Flavobacterium degerlachei [ 63 ], Arthrobacter agilis [ 64 ], Micrococcus luteus [ 21 ], and Leifsonia rubra [ 14 , 65 ] from water, soil, and animal samples of polar origin. The species Pseudomonas lundensis , Pseudomonas peli [ 25 ], Acinetobacter lwoffii [ 66 ], Sporosarcina globispora [ 67 ], Carnobacterium inhibens [ 68 ], Arthrobacter alpinus [ 69 , 70 ], and Arthrobacter agilis were isolated from cold non-polar environments such as frozen food, non-polar permafrost sediments, glaciers, glacial currents, a subglacial lake in the Himalayas, and Siberian permafrost.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, that bacterial species isolated from MPs in this study were previously found in both cold and non-cold environments, while most of the isolated bacterial species were similar to those found in other types of samples from cold polar and non-polar regions. For example, other researchers isolated Shewanella baltica [ 58 ], Pseudomonas lundensis [ 59 , 60 ], Pseudomonas leptonychotis [ 61 ], Carnobacterium funditum [ 62 ], Carnobacterium iners , Flavobacterium degerlachei [ 63 ], Arthrobacter agilis [ 64 ], Micrococcus luteus [ 21 ], and Leifsonia rubra [ 14 , 65 ] from water, soil, and animal samples of polar origin. The species Pseudomonas lundensis , Pseudomonas peli [ 25 ], Acinetobacter lwoffii [ 66 ], Sporosarcina globispora [ 67 ], Carnobacterium inhibens [ 68 ], Arthrobacter alpinus [ 69 , 70 ], and Arthrobacter agilis were isolated from cold non-polar environments such as frozen food, non-polar permafrost sediments, glaciers, glacial currents, a subglacial lake in the Himalayas, and Siberian permafrost.…”
Section: Discussionmentioning
confidence: 99%
“…The psychrophiles have been considered to possess the ability of tolerating far higher temperature ranges than the real ambient temperature from which they were isolated, when cultivated in-vivo ( Cavicchioli, 2016 ); for example, P. psychrophila MTCC12324 ( Abraham et al, 2020 ) and P. frederiksbergensis ( Cui et al, 2022 ) etc., were observed to grow between 4–37°C, Pseudomonas sp. 30–3 with a survival range of 0–35°C retrieved from oil-affected soil, Wright Valley, Antarctica ( Panicker et al, 2002 ); P. lundensis, isolated from Antarctic meltwater pond was also reported to survive at 0°C ( Ravi et al, 2022 ). Similarly, pH is another important factor regulating the survival and growth of microorganisms in extreme climatic conditions.…”
Section: Factors Regulating Microbial Diversity In Cold Environmentsmentioning
confidence: 99%
“…Most often, these types of microbiota colonize low-temperature areas like snow, permafrost, sea ice, and glaciers (10). For example, Joshi (6) reported minimal growth below 15°C and optimal growth at 25°C, while Ravi et al, (11) reported an upper growth limit of 37°C. This established the fact that growth temperature range varied between the bacterial species, leading to a division into psychrophilic and psychrotolerant strains (7).…”
Section: Cold-adapted Bacteriamentioning
confidence: 99%